Optimization of Off-Centre bracing system using Genetic Algorithm - Yazdi, H.A. Mosalman; Ramli Sulong, Nor Hafizah (Elsevier, 2011)
In this paper, a method based on genetic algorithm is proposed for determining the optimum connection point with the highest lateral buckling load in the Off-Centre bracing system. This type of bracing system is mostly used in seismic areas and it allows architects to have more openings in the panel area. In this system, the non-straight diagonal member introduces eccentricity to the system and is connected to the corner of the frame by a third member. In designing this system, designers often use "trial and error" to locate the connection point of the brace elements considering various parameters affecting the design such as opening and frame dimensions, cross sectional areas of brace elements and the location of the brace element connection. Hence, finding the best connection point with maximum lateral buckling load can be problematic by the conventional methods. To demonstrate the effectiveness of the proposed GA method, examples with different frame specifications were presented. © 2011 Elsevier Ltd. All rights reserved.